Management Implementation Mechanism for SMA Jaya Langsa City - Wiriani, Erni (JOURNAL INCLUSIVE SOCIETY COMMUNITY SERVIES, 2024)
Performance management at SMA JAYA Langsa is very important in achieving organizational goals. With employees carrying out certain tasks and functions, planning and implementing programs becomes crucial to achieving the desired goals. A clear division of tasks is needed to ensure employee work effectiveness. The development of science and technology challenges leaders and employees to make the right decisions, which are influenced by education, the environment and technological advances. In implementing performance management at SMA JAYA Langsa, it is necessary to strengthen the potential of each employee, increase the quality and quantity of work, and ensure consistent attendance.